Jini out of the bottle. (Economist, 1999)
Focuses on Bill Joy, chief scientist at Sun Microsystems and the inspiration behind the software technology called Jini. How Jini could change the way computers work; Joy's view that operating systems are hopelessly complex; Sun's Java, a universal language for software; How Jini creates a universal language for hardware; How Jini could transform the economics of computing; Sun's rivalry with Microsoft.